2017
DOI: 10.3389/fpsyg.2017.00447
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent Effect of Arousal on Early Auditory Perception

Abstract: Mood has been shown to influence cognitive performance. However, little is known about the influence of mood on sensory processing, specifically in the auditory domain. With the current study, we sought to investigate how auditory processing of neutral sounds is affected by the mood state of the listener. This was tested in two experiments by measuring masked-auditory detection thresholds before and after a standard mood-induction procedure. In the first experiment (N = 76), mood was induced by imagining a moo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
0
4
1
Order By: Relevance
“…These conclusions from our results relate to the findings of a recent study that also points to different induced moods influencing masked auditory detection thresholds in humans. However, somehow, their data did not allow for drawing unequivocal conclusions (Bolders et al, 2017). Our findings of lower auditory emotion detection sensitivity with higher anxiety are in contrast to earlier reports of enhancements in visual sensitivity with greater anxiety, especially for negative stimuli (Byrne and Eysenck, 1995;Bradley et al, 1998;Fox, 2002;Richards et al, 2002;Koster et al, 2006b;Bar-Haim et al, 2007;Doty et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…These conclusions from our results relate to the findings of a recent study that also points to different induced moods influencing masked auditory detection thresholds in humans. However, somehow, their data did not allow for drawing unequivocal conclusions (Bolders et al, 2017). Our findings of lower auditory emotion detection sensitivity with higher anxiety are in contrast to earlier reports of enhancements in visual sensitivity with greater anxiety, especially for negative stimuli (Byrne and Eysenck, 1995;Bradley et al, 1998;Fox, 2002;Richards et al, 2002;Koster et al, 2006b;Bar-Haim et al, 2007;Doty et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…The fact that the effects in our data were observed with predominantly negative, threatening affective signals (Disgust and Fear) could be explained on the premise that such environmental stimuli are processed faster and with more efficiency in the brain towards influencing behaviour [46]. These conclusions from our results advance the findings of a recent study that also points at different induced moods influencing masked auditory detection thresholds in humans but somehow their data did not allow drawing unequivocal conclusions [47].…”
Section: Discussioncontrasting
confidence: 58%
“…And varying levels of arousal induced by valenced pictures were observed to alter participants' perception of height [28]. Strikingly, a recent human auditory study indicated that the auditory masking threshold varied markedly with rated emotional arousal [29]. Such findings are mirrored in the animal literature, demonstrating that emotional arousal enhances the activity of the primary auditory cortex (A1) and enhances the connection between A1 and the medial prefrontal cortex [30].…”
mentioning
confidence: 92%